Capturing the Emergence of Change in Complex Systems: The ‘Atawhai’ Study in Aotearoa, New Zealand - Gear, Claire; Koziol-McLain, Jane; Eppel, Elizabeth; Hape, Hazel; Rolleston, Anna; Manuel, Carey; Timutimu, Ngareta; Ahomiro, Hori; Healy, Clare; Isham, Claire (SAGE Publications, 2025)
A wide range of evaluative evidence is necessary to capture change within complex systems as findings shape the form and interpretation of outcomes, how they are valued, and actions moving forward. The Atawhai study worked with primary health care professionals in a series of workshops to distil ways to make it easier to respond to family violence as a key determinant of ill health. This article describes three methods used to evaluate the emergence of change from the perspective of the Atawhai research participants including pre/post-readiness surveys, social network analysis and qualitative exit interviews. Each method provides a unique perspective on the complexity involved and triangulation across the methods indicates validation of findings. Capturing change within complex systems requires methodological agility and overlaying of diverse evidence. The contribution of ‘soft infrastructure’ in developing and sustaining complex interventions should not be underestimated.
Keywords: 4404 Development Studies; 4409 Social Work; 4410 Sociology; 44 Human Society